Probabilistic risk assessment and management for engineers and scientists - Kumamoto, Hiromitsu (IEEE Press, 1996)
Completely updated and revised, this modern, computer-based text. helps develop synthesis and analysis methods for risk and reliability studies from fundamental principles, and apply them to realistic industrial-level problems. The full treatment of qualitative analysis methods includes: fault trees, FMEA, event trees, decision labels, cause-consequence charts and common-mode failures. In addition, quantitative system analysis techniques - kinetic tree theory, cut set and prime implicant analysis and Markov and Monte Carlo methods - are thoroughly covered and developed.